Historical Review of Secondary Entry Flows in Polymer Melt Extrusion. (3rd April 2019) - Musil, Jan; Zatloukal, Martin
Abstract: Secondary flow (also termed as stagnation flow, dead space, recirculation zone, and vortex) is rheological phenomenon occurring during flow of polymer melts through abrupt contraction channels as result of flow separation from solid boundary leading to accelerating flow regime with recirculating material in corners. Polymer melt captured in secondary flow slowly rotates in direction opposite to main flow direction and simultaneously moves in third direction through helical motion. This may first reduce flow stability and second increase residence time initiating highly undesirable thermal degradation of polymer melt. Since the first visual experimental observation performed by Tordella and preliminary theoretical prediction made by Langlois and Rivlin at the end of the 1950s, this phenomenon represents one of the most fundamental rheological problems ever with many practical and theoretical impacts discussed here. This comprehensive review written in historical perspective summarizes key factors (Newtonian viscosity, shear thinning, viscoelasticity, flow geometry, and extensional viscosity) influencing secondary entry flows for polymer melts and provides deep and critical discussion of the most important experimental and theoretical works on this topic (such as branched low-density polyethylene, LDPE, linear low-density polyethylene, LLDPE, high-density polyethylene, HDPE, polystyrene, PS, isotactic polypropylene, PP, polymethyl methacrylate, PMMA, polyamide, Nylon PA 66, or polybutadiene, BR).